Analisis Kepuasan Wisatawan Terhadap Produk Wisata dan Strategi Pengembangan DTW Telaga Wopersnondi Biak Timur - Salakory, Hans S. M.; Matulessy, Febby Sonya; Saragih, Yansen M. I (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i02.p18, 2020)
Visitors of Wipersnondi Lake had great hope of fulfilling their comfort when they arrived at the tourism sites, in fact the performance felt by visitors cannot satisfy all the expectations of visitors and had  impact  on their satisfaction and convenience. This study aims to determine the level of satisfaction of tourist visitors to the availability of elements of tourism products, and to find out its developments strategy. To answer the research problem, the analysis technique used is Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results of research based on CSI show that visitors are not satisfied with the performance of tourism products at Wopersnondi Lake.  Based on the results of the IPA analysis, the main priorities for tourism development in Wopersnondi Lake are increasing affordability and opening of public transport routes, improving cleanliness and increasing the number of toilets, specifically at the lake location, providing road directions to the location, and building health facilities like public health centers around Wopersnondi Lake. Furthermore, the unique aspects of  Wopersnondi Lake that must be maintained are the beautiful view at the tourist location, the comfort of the tourist attraction, the coolness, the cleanliness, the quality of the road to the lake, the parking lot area, and the availability of trash cans are things that have actually been felt and have created comfort and  good experience for visitors to Wopersnondi Lake.  This development must support the development of other tourism products.. Key Word : Importance  Performance  Analysis, Customer Satisfaction Index.